A Multifunctional Nanoplatform against Multidrug Resistant Cancer: Merging the Best of Targeted Chemo/Gene/Photothermal Therapy. (10th October 2017) - Cheng, Wei; Nie, Junpeng; Gao, Nansha; Liu, Gan; Tao, Wei; Xiao, Xiaojun; Jiang, Lijuan; Liu, Zhigang; Zeng, Xiaowei; Mei, Lin
Abstract: Synergistic therapy that combines chemo‐, gene‐, or photothermal means shows great potential for enhancing the therapeutic effects on cancers. Tumor‐targeted nanoparticles based on a doxorubicin (DOX)‐gated mesoporous silica nanocore (MSN) encapsulated with permeability glycoprotein (P‐gp) small interfering RNA (siRNA) and a polydopamine (PDA) outer layer for DOX loading and folic acid decoration are designed. The multifunctional nanoplatform tactfully integrates chemo‐ (DOX), gene‐ (P‐gp siRNA), and photothermal (PDA layer) substances in one system. In vitro results reveal that DOX release behaviors are both pH‐ and thermal‐responsive and the release of co‐delivered P‐gp siRNA is also pH‐dependent due to the pH‐cleavable DOX gatekeeper on MSN. In addition, due to the near‐infrared light‐responsive PDA outer layer and folic acid conjugation, the nanoparticles exhibit outstanding photothermal activity and selective cell targeting ability. Subsequently, in vitro and in vivo antitumor experiments both demonstrate the enhanced antitumor efficacy of the multifunctional nanoparticles, indicating the significance of synergistic therapy combining chemo‐, gene‐, and photothermal treatments in one system. Abstract : A novel drug and siRNA codelivery system based on polydopamine‐coated drug‐self‐gated mesoporous silica is developed. This drug delivery platform possesses three different therapeutic effects: chemo‐, gene‐, and photothermal therapy. Moreover, this nanosystem with tumor‐targeting and pH‐responsive abilities is also endowed. The enhanced tumor therapy effect is demonstrated by both in vitro and in vivo studies.